Evaluating the Effectiveness of Cisco Packet Tracer for Teaching Networking Concepts at the Undergraduate Level - Saud, Arjun Singh; Adhikari, Binod; Piya, Subeksha (Perspectives on Higher Education, 2025)
This research aimed to examine whether Cisco Packet Tracer (CPT) leads to improved student achievement. Additionally, the study explored student’s attitudes towards CPT during their networking learning experience. Employing a quasi-experimental quantitative research design, the study utilized a demonstrative and collaborative teaching approach based on Vygotsky's Social Constructivist learning theory. Twenty two students from Chitwan district of Nepal were purposively selected for the study. Multiple-choice questions for achievement test and five point likert scale for analyzing attitude towards CPT was used in the study. Pretest and posttest achievement test items were developed using scholarly and peer suggestions, followed by a pilot test. The data obtained from the achievement test and opinionnaire were analyzed using inferential and descriptive statistics. The finding of the study indicates that the student of experimental group has better performance than control group. In the Likert scale questionnaire conducted solely on the experimental group, students' attitudes toward Cisco Packet Tracer appeared positive, showing increased interest, engagement, and confidence when dealing with real physical devices.